The impact of large claims on actuarial decisions - Tartaľová, Alena (Wpływ występowania wysokich szkód na decyzje aktuarialne, 2010)
The article discusses the application of extreme value theory in the analysis of extreme values what makes their statistical analysis easier. The application of this method in the analysis of reinsurance contracts, reinsurance of loss excess and excess of loss ratio is described. Furthermore, in the case of agreements of the reinsurance of loss excess two ways of establishing an optimal level of retention are analyzed
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 106, s. 150-158